WHEELSET AXLE WITH THE CAVITY OF UNIFORM CROSS SECTION - Kolesnykov, S. R.; Romaniukha, M. R.; Kebal, I. Yu. (Science and Transport Progress, 2014)
Purpose. Due to operation in complex loading conditions, the rolling stock wheelsets should provide high reliability, since the train traffic safety largely depends on them. Design and technical condition of wheelsets affect the smoothness, intensity of forces generated by the interaction between the car and track, and the motion resistance. Specificity of the axle operation consists in the fact that it undergoes the bending stresses under loading. These stresses are unevenly distributed along the cross-sectional area, reaching the highest values in the outer fibers and the minimal values in the internal ones. This aspect sets the problem of replacement of the uniform cross section with the hollow cross section. The disadvantages of hollow axle design, which are used at the present time, should include a significant manufacturing complexity of the variable section cavity. The purpose is to develop a modernized design of the wheelset axle. Methodology. A construction of the hollow axle having an inner longitudinal cylindrical through hole of the constant diameter throughout its length was proposed. The item is made of steel seamless tube. The inner surface of the tube is treated by mechanical means to remove the voltage concentrations in the internal longitudinal cylindrical through hole, which has a constant diameter along the entire length of the axle. Findings. Application of this design will facilitate manufacturing of the hollow axle and the machining of the inner longitudinal through hole, while retaining all the use advantages of the hollow axle in the rolling stock wheel pairs. Another use advantage of the hollow axle of this design is the absence of partial heterogeneity of the metal, which is inevitably, occurs during the solid axles blanking. Originality. A new design of the wheelset hollow axle of railway rolling stock was proposed. Practical value. Introduction of the new design simplifying the manufacture and mechanical treatment of the inner cavity of the wheel pair axle will bring significant economic benefits. According to preliminary calculations, the use of the axle with the uniform cross section cavity will reduce the metal consumption by 100-110 kg.